Induction of Mast Cell Accumulation by Tryptase via a Protease Activated Receptor-2 and ICAM-1 Dependent Mechanism. (9th June 2016) - Liu, Xin; Wang, Junling; Zhang, Huiyun; Zhan, Mengmeng; Chen, Hanqiu; Fang, Zeman; Xu, Chiyan; Chen, Huifang; He, Shaoheng
Abstract : Mast cells are primary effector cells of allergy, and recruitment of mast cells in involved tissue is one of the key events in allergic inflammation. Tryptase is the most abundant secretory product of mast cells, but little is known of its influence on mast cell accumulation. Using mouse peritoneal model, cell migration assay, and flow cytometry analysis, we investigated role of tryptase in recruiting mast cells. The results showed that tryptase induced up to 6.7-fold increase in mast cell numbers in mouse peritoneum following injection. Inhibitors of tryptase, an antagonist of PAR-2 FSLLRY-NH2, and pretreatment of mice with anti-ICAM-1, anti-CD11a, and anti-CD18 antibodies dramatically diminished tryptase induced mast cell accumulation. On the other hand, PAR-2 agonist peptides SLIGRL-NH2 and tc-LIGRLO-NH2 provoked mast cell accumulation following injection. These implicate that tryptase induced mast cell accumulation is dependent on its enzymatic activity, activation of PAR-2, and interaction between ICAM-1 and LFA-1. Moreover, induction of trans-endothelium migration of mast cells in vitro indicates that tryptase acts as a chemoattractant. In conclusion, provocation of mast cell accumulation by mast cell tryptase suggests a novel self-amplification mechanism of mast cell accumulation. Mast cell stabilizers as well as PAR-2 antagonist agents may be useful for treatment of allergic reactions.